Identification of oncofetal PIWI-interacting RNAs as potential prognostic biomarkers in non-small cell lung cancer - Pewarchuk, Michelle E.; Souza, Vanessa G. P.; Cohn, David E.; Telkar, Nikita; Stewart, Greg L.; Bénard, Katya H.; Reis, Patricia P.; Martinez, Victor D.; Robinson, Wendy P.; Lam, Wan L. (Frontiers in Genetics, 2025)
Lung cancer is the leading cause of cancer-related deaths worldwide, with non-small cell lung cancer (NSCLC) accounting for the majority of these cases. Despite advancements in targeted therapies, early detection remains a significant challenge, highlighting the need for novel biomarkers. This study investigates the role of PIWI-interacting RNAs (piRNAs) in lung cancer, specifically focusing on their potential as oncofetal biomarkers in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), the two most common histological subtypes of NSCLC. We hypothesize that piRNAs exhibit oncofetal expression patterns and may contribute to lung cancer development. Through bioinformatics analysis, we identified distinct piRNA profiles in non-neoplastic, malignant, and fetal lung tissues. Among these, 37 piRNAs in LUAD and 46 piRNAs in LUSC displayed oncofetal expression, meaning they were present in tumor tissues but absent in adjacent normal lung tissue. These oncofetal piRNAs showed significant prognostic value in both LUAD and LUSC cohorts, with a specific signature of eight oncofetal piRNAs predicting high-risk patients in LUAD. We validated the robustness of this signature in a separate in-house cohort, which underscores its potential as a prognostic biomarker. Our findings suggest that oncofetal piRNAs could offer new diagnostic and therapeutic opportunities, particularly for early detection.